2017
DOI: 10.1155/2017/6721354
|View full text |Cite
|
Sign up to set email alerts
|

Association between Soil Fertility and Growth Performance of Planted Shorea macrophylla (de Vriese) after Enrichment Planting at Rehabilitation Sites of Sampadi Forest Reserve, Sarawak, Malaysia

Abstract: A study was conducted to determine the status of soil properties after enrichment planting in comparison to an adjacent secondary forest and to evaluate the effect of enrichment planting of Shorea macrophylla (de Vriese) on the soil fertility status with special reference to Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF) at Sampadi Forest Reserve, Sarawak. The study sites were stands rehabilitated in different years (1996: SM96; 1997: SM97; 1998: SM98; 1999: SM99) and secondary forest (SF). Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 51 publications
3
21
1
Order By: Relevance
“…We saw that soil pH decreased with increasing age of the planted stands, supporting Aweto (1981), Perumal et al (2017), and Li et al (2013) who observed a decline in soil pH over 10, 18, and 30 years, respectively, as result of a succession. We showed that this decline continued with age.…”
Section: Discussionsupporting
confidence: 85%
“…We saw that soil pH decreased with increasing age of the planted stands, supporting Aweto (1981), Perumal et al (2017), and Li et al (2013) who observed a decline in soil pH over 10, 18, and 30 years, respectively, as result of a succession. We showed that this decline continued with age.…”
Section: Discussionsupporting
confidence: 85%
“…Soil pro le description was conducted at the study sites for the identi cation of soil types [46]. Subsequently, undisturbed core samples (100 g•mL −1 ) were collected from 0-10 cm depth and 30-40 cm depth in triplicates for soil bulk density determination [47]. Soil hardness was determined using Yamanaka-type push cone penetrometer.…”
Section: Soil Sample Collection and Analysismentioning
confidence: 99%
“…However, in our recent study it was stated that the root of S. macrophylla trees was able to survive and grow under waterlogged soil conditions with a low availability of oxygen [10]. Thus, S. macrophylla not only is considered as shade tolerant species but also can be considered as flood tolerant tree [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our group [10,11,15] and others [6,[16][17][18] starting in the year 1999 have emphasized determining suitable species for enrichment planting in relation to the growth performance, planting techniques, and soil characteristics. Thus, this study was conducted due to a gap in the information available on the potential of indigenous tree species after enrichment planting for restoration ecology in riparian areas.…”
Section: Introductionmentioning
confidence: 99%